Preparation of ZnO/Brucite Functional Composite Powder by the Mechanochemical Method - Shuai, Huan; Wang, Jiao; Ren, Fengguo; Du, Gaoxiang (Frontiers in Materials, 2021)
In this experiment, ZnO/brucite composite powder was prepared through the mechanochemical method; further, the properties, particle morphology, and structure of the composite powder were characterized. The results show that mechanical grinding action can promote the production of a large number of surface ions with unsaturated coordination number on the surface of brucite and ZnO particles, thereby promoting hydroxylation of the particle surfaces. The addition of NaOH to the composite system can also aid the further activation of the surface of the brucite and ZnO particles and the formation of more associated hydroxyl groups. Finally, a core–shell composite powder is formed with weak forces such as hydrogen bonds and van der Waals forces as the connecting bonds.